The importance of urotensin II level in the diagnosis of acute mesenteric ischemia - Çay, Ferhat Çay; Çetinkaya, Hasan Basri; Duran, Ali; Kuloğlu, Tuncay; Kanat, Burhan Hakan; Ustundag, Bilal (My University, 2022)
Aim: This study was conducted to investigate the diagnostic importance of Urotensin II (UT-II) levels, which cause vasodilation as a compensation mechanism in the early phase of Acute Mesenteric Ischemia (AMI). For this purpose, human plasma urotensin was studied for the first time in the literature for the early diagnosis of mesenteric ischemia. Material and Method: The study consisted of 60 patients. The patients were divided into three groups: Group 1: group with mesenteric ischemia (n: 20); Group 2: group with abdominal pain and with no mesenteric ischemia (n: 20); Group 3: control group with no complaints (n: 20). The blood samples were taken from the patients through peripheral venous access, and Urotensin II (UT-II), Aspartate Aminotransferase (AST), Alkaline phosphatase (ALP), Lactate, and D-dimer levels were measured. Results: While a significant increase was found between Group1 and Group 2 and between Group1 and Group3 in terms of UT-II values (p0.05). A significant increase was found between Group1 and Group2 and between Group1 and Group3 regarding AST values (p0.05). There was a significant increase between Group1 and Group3 in terms of D-dimer values (p0.05). There was no significant difference between the groups concerning ALP and Lactate values (P>0.05). Conclusion: It was concluded that UT-II could be used in the diagnosis of AMI but that there was a need for comprehensive studies investigating the changes in ischemia time-related UT-II serum levels.
Keywords: D-dimer; Acute Mesenteric Ischemia; Urotensin-II